Reflexiv handlungsfähig Entwicklungslinien und Ergebnisse der Lehrkräftebildung an der Leibniz Universität Hannover - Gillen, Julia; Labede, Julia; Lindmeier, Bettina; Müller, Katharina; Nehring, Andreas; Schanze, Sascha (Beiträge zur Pädagogik, 2023)
The volume documents the institutional, cross-phased and teaching and teacher training related reform initiatives of the project "Leibniz-Prinzip" funded by the "Qualitätsoffensive Lehrerbildung". The variety of reform efforts in teacher education at Leibniz Universität Hannover is presented by means of three virulent requirement areas of university teacher education: 1. heterogeneity and diversity, 2. modern (digitally supported) teaching-learning formats, 3. practice phases and transfer. In orientation to the guiding principle of reflexive action, teaching and teaching concepts, research results as well as institutional developments are discussed and put into perspective. With contributions by Alena Beck | Tabea Becker | Andrea Bernholt | Anja Binanzer | Marcel Bonorden | Sarah Dannemann | Kathleen Ehrhardt | Sarah Fox | Monika E. Fuchs | Bettina Gautel | Julia Gillen | Sandra Günter | Benjamin Haag | Caroline Hagemeier | Robert Marten von der Heide | Gudrun Heuschen | Reinhard Hochmuth | Thomas N. Jambor | Felix Kappeller, M.A. | Sarah Khellaf | Melanie Korn | Alexandra Krüger | Julia Labede | Bettina Lindmeier | Christiane Meyer | Stephanie Mittrach | Katharina Müller | Andreas Nehring | Tjark-Gerit Neugebauer | Helene Pachale | Johannes Paehr | Jutta Papenbrock | Andrea Rössler | Nina Rothenbusch | Alisa Schafferschik | Sascha Schanze | Claudia Schomaker | Heidi Seifert | Tabea Taulien | Sabine Vogelsang, M.A. | Andreas Wernet | Rolf Werning | Ketevan Zhorzholiani-Metz